2003
DOI: 10.1034/j.1399-5448.2003.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin: obesity, diabetes and other peripheral effects - a review

Abstract: There is an increasing epidemic of obesity in the Western and developing world that has not spared children and, hence, is of great concern. Obesity presents numerous physiological and psychosocial problems for the child. Childhood obesity not only increases the risk of obesity in adulthood, it is associated with type 2 diabetes mellitus; is the leading cause of pediatric hypertension; increases the risk of coronary heart disease; and increases stress on the weight-bearing joints. Social and psychological prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 113 publications
3
72
0
3
Order By: Relevance
“…Fasting plasma insulin was also decreased in aP2-G0S2 mice, which is further suggestive of a more insulin responsive animal. Furthermore, changes in plasma adipokines including an increase in leptin and an accompanying decrease in adiponectin are consistent with elevated adiposity (32,33). Even with the reduction in plasma adiponectin levels, however, we have found no significant up-regulation of proinflammatory genes (Table 1) or morphological indications of increased inflammation in WAT (data FIGURE 5.…”
Section: Discussionsupporting
confidence: 57%
“…Fasting plasma insulin was also decreased in aP2-G0S2 mice, which is further suggestive of a more insulin responsive animal. Furthermore, changes in plasma adipokines including an increase in leptin and an accompanying decrease in adiponectin are consistent with elevated adiposity (32,33). Even with the reduction in plasma adiponectin levels, however, we have found no significant up-regulation of proinflammatory genes (Table 1) or morphological indications of increased inflammation in WAT (data FIGURE 5.…”
Section: Discussionsupporting
confidence: 57%
“…45 Leptin has effects on different systems of the body: central nervous system (inhibition of food intake, reduction of adipose mass and increased thermogenesis), glucose homeostasis, reproductive system (signalling onset of puberty and maintenance of reproductive function), autonomic nervous system, hematopoietic system, skeletal system, oncogenesis and transplantation (contributing to rejection of transplants). 46 Our results show that leptin levels are directly associated with MetS, BMI, blood pressure and inactivity also among adolescents. Previous findings pointed out that girls showed higher levels of leptin than boys independently of the degree of obesity; 47 however, we just found these results among normal weight adolescents.…”
Section: Inflammatory Markers M Gonzá Lez Et Alsupporting
confidence: 49%
“…Numerous publications in adults suggest leptin as a biomarker for obesity, insulin resistance and MetS. 12,13 PAI-1 is a pro-inflammatory adipokine with pro-thrombotic effects that is also increased in obesity, including children and adolescents when compared with a control group. 14 Some studies have reported an association between PAI-1 and the prevalence of MetS, including adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is supposed that obese patients are resistant to leptin, just as in type 2 diabetes, where insulin resistance is observed [63,76,78]. Furthermore, hyperleptinemia caused by obesity is an important risk factor leading to the development of type 2 diabetes [79].…”
Section: Leptinmentioning
confidence: 99%